Critical border studies : broadening and deepening the 'Lines in the Sand' agenda / edited by Noel Parker and Nick Vaughan-Williams. - Parker, Noel, 1945-; Vaughan-Williams, Nick (Routledge, 2014)
This edited collection formalises Critical Border Studies (CBS) as a distinctive approach within the interdisciplinary border studies literature. Although CBS represents a heterogeneous assemblage of thought, the hallmark of the approach is a basic dissatisfaction with the 'Line in the Sand' metaphor as an unexamined starting point for the study of borders. A headline feature of each contribution gathered here is a concerted effort to decentre the border.